Study of microbial growth on silicone tubes after transcanalicular laser-assisted dacryocystorhinostomy and correlation with patency - Goel, R; Nagpal, S; Kamal, S; Kumar, S; Mishra, B; Loomba, P S (Nepalese Journal of Ophthalmology, 2017)
Introduction: Intubation in primary transcanalicular laser assisted dacryocystorhinostomy (TCLADCR) is performed to increase the success rates. However, the associated inflammation and infection can have adverse effects. Objective: To study the microbial infection and drug susceptibility of extubated silicone tubes and final anatomical patency in patients undergoing TCLADCR. Materials and methods: A non-randomised prospective interventional study was conducted in a tertiary care eye centre. The study included twenty consecutive adult patients with primary nasolacrimal duct obstruction. They underwent TCLADCR with bicanalicular silicone intubation. The stents were removed at 2 months and subjected to culture sensitivity, followed by administration of appropriate antimicrobial agents. Main outcome measures studied were the microbial spectrum on the cultured tubes, their sensitivity profile and its correlation with final anatomical patency. Results: A positive culture was obtained in 100% cases, comprising of normal commensals and pathogenic organisms. Of the total 24 isolates, 16 (66.6%) Gram positive bacteria (75% Staphylococcus aureus) and 8 (33.3%) Gram negative bacteria (commonest E.coli) were found, with 4 tubes having more than one isolate. No fungal growth was seen. Ninety percent success rate was achieved at one year following appropriate antimicrobial therapy except in 2 patients with gram negative isolates who had failed to take the prescribed antibiotics following sensitivity reports. There was no correlation between multiple infections and success rate. However, by using the Fisher exact test, a positive correlation was obtained between appropriate antibiotic treatment and the final anatomical patency (p